PHYSIOLOGICAL RESPONSE AND GROWTH PERFORMANCE OF SPINY LOBSTER (Panulirus homarus) JUVENILE REARING IN RECIRCULATING AQUACULTURE SYSTEM WITH VARIOUS SHELTER TYPE - Adiyana, Kukuh; Zulkarnain, Riza; Thesiana, Lolita (Marine Research in Indonesia, 2019)
Spiny lobster nursery is done to produce more adaptive and uniform juvenile lobsters quality. Shelters used in spiny lobster nursery served to reduce physical contact among lobsters in rearing tank. The purpose of this study was to analyze the effect of different shelter types on physiological response and growth of spiny lobster (Panulirus homarus) juvenile rearing in recirculating aquaculture system. Lobsters with an average weight 51,29 ± 7,26 gram, were reared for 60 days. They were feed once a day with trash fish. Daily feeding rate was 3-4%  of total weight.This study used four types of shelter as treatments with two replications. PVC pipe shelter as control (K), individual shelter square shaped (IS ?), individual shelter triangle shaped (IS ?) and individual shelter  tube shaped (IS ?).The results of this study showed that IS ?  used  in   rearing Panulirus homarus showed lower stress response than the other treatments, in terms of glucose.and total protein lobster hemolymph during the study. IS ? is the best, because it reduced stress level and yielded better total biomass among the other treatments.